DAMPAK PEREKONOMIAN PENGGUNAAN TENAGA KERJA ASING DI LOMBOK TIMUR - Ahmad Rosidi (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2019)
This writing aims to find out 1) What factors are behind the increasing number of foreign workers in the East Lombok Region. 2) what is the effort of the East Lombok Regency Government to protect local workers from the rush of foreign workers in the East Lombok Regency. This research was conducted with the "empirical normative" method or literature study and added empirical elements, which collected material from literature both in hardcopy and softcopy and normatively analyzed with the study of international law and Indonesian national law and by adding empirical elements. The results obtained are as follows: 1) Factors affecting the increasing number of foreign workers in the East Lombok regency can be found in Law No. 25 of 2007 concerning Foreign Investment, a book on legal aspects of investment and interviews with foreign labor inspector officials in East Lombok. The implementation of GATS in Indonesia requires the existence of a free market which means that more foreign workers will enter Indonesia. 2) the government's effort to protect local workers from the entry of foreign workers, by issuing a more selective policy on the supervision of foreign workers entering and work to Indonesia by issuing Presidential Decree No.20 of 2018 on Foreign Workers and implementing regulations Permenaker No, 10 of 2018 concerning How to use TKA. In this Permenaker, various regulations that tighten the use of TKA are covered